Key factors of desiccant-based cooling systems: Materials - Asim N.; Amin M.H.; Alghoul M.A.; Badiei M.; Mohammad M.; Gasaymeh S.S.; Amin N.; Sopian K. (Elsevier Ltd, 2023)
Air conditioning; Carbon; Cooling; Driers (materials); Humidity control; Materials; Silica; Thermoelectric equipment; Desiccant; Desiccant air-conditioning systems; Desiccant cooling; Desiccant cooling systems; Environmental conditions; Optimal performance; Preparation; Temperature and humidities; Cooling systems